2008
DOI: 10.1080/13651500701422622
|View full text |Cite
|
Sign up to set email alerts
|

Insight in first-episode schizophrenia

Abstract: Objective. To compare insight impairment, including its temporal changes, between remitters and nonremitters in patients with first-episode schizophrenia. Method. Males, consecutively hospitalized with diagnosed first-episode schizophrenia (according to ICD 10), who provided written informed consent, and were reassessed at the 1-year follow-up were included. The psychopathology was evaluated using the Positive and Negative Syndrome Scale (PANSS) prior to acute treatment - on admission; at the end of the acute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…10 This confirmed earlier work in studies using mostly cross-sectional designs and prevalent cases, 14,[20][21][22][23][24][25][26][27] plus prospective studies. 8,[28][29][30] Gharabawi et al carried out secondary analyses on an open-label multicentre trial of long-acting risperidone injection, and found that change on the insight item from the Positive and Negative Syndrome Scale (PANSS) for schizophrenia correlated with change in Clinical Global Impression-Severity (CGI-S) scores at 1 year, but not with quality of life. 28 Saeedi et al reported on 278 patients admitted to a Canadian early psychosis service.…”
Section: Discussionmentioning
confidence: 99%
“…10 This confirmed earlier work in studies using mostly cross-sectional designs and prevalent cases, 14,[20][21][22][23][24][25][26][27] plus prospective studies. 8,[28][29][30] Gharabawi et al carried out secondary analyses on an open-label multicentre trial of long-acting risperidone injection, and found that change on the insight item from the Positive and Negative Syndrome Scale (PANSS) for schizophrenia correlated with change in Clinical Global Impression-Severity (CGI-S) scores at 1 year, but not with quality of life. 28 Saeedi et al reported on 278 patients admitted to a Canadian early psychosis service.…”
Section: Discussionmentioning
confidence: 99%
“…A higher score on this item reflects less acceptance and insight into having a psychiatric illness and needing treatment. Ceskova et al 10 have demonstrated the validity of the PANSS insight (G12) item in first-episode psychosis.…”
Section: Methodsmentioning
confidence: 99%